2002
DOI: 10.1128/jvi.76.4.1971-1979.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Varicella-Zoster Virus: Evidence of Intercontinental Spread of Genotypes and Recombination

Abstract: A heteroduplex mobility assay was used to identify variants of varicella-zoster virus circulating in the United Kingdom and elsewhere. Within the United Kingdom, 58 segregating sites were found out of the 23,266 examined (0.25%), and nucleotide diversity was estimated to be 0.00063. These are an order of magnitude smaller than comparable estimates from herpes simplex virus type 1. Sixteen substitutions were nonsynonymous, the majority of which were clustered within surface-expressed proteins. Extensive genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 49 publications
6
103
2
1
Order By: Relevance
“…The VZV genome is so highly conserved that the most distantly related genotypes examined in this study (J and M1) differed by only ϳ0.2%. In a comparison between the European strain Dumas, the Japanese strain P-Oka and the mixed (25,30), the VZV selected strains segregated into at least three genotypes. We performed phylogenetic analyses based on the complete genome (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The VZV genome is so highly conserved that the most distantly related genotypes examined in this study (J and M1) differed by only ϳ0.2%. In a comparison between the European strain Dumas, the Japanese strain P-Oka and the mixed (25,30), the VZV selected strains segregated into at least three genotypes. We performed phylogenetic analyses based on the complete genome (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was demonstrated that sequence analysis of a 447-nucleotide (nt) region located in open reading frame 22 (ORF22r1) could unerringly recapitulate the genotyping results obtained from analyzing 23 single-nucleotide polymorphisms located in seven open reading frames distributed over the entire genome. These analyses implied that recombination events, which were recently found to be a common feature among wild-type isolates of another alphaherpesvirus, i.e., herpes simplex virus type 1 (5, 31), were of interest for future study as a possible mechanism for VZV strain variation (30). In the studies reported here, we determined the complete genomic sequence of two M VZV strains presented in a previous study (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2. lation as one of dominant virus species. Hitherto intraspecies recombinants have been reported including HSV-1, VZV, and EBV (22)(23)(24)38). On the other hand, interspecies recombinants have been regarded to survive rarely in nature (5).…”
Section: Discussionmentioning
confidence: 99%
“…The genome of VZV contained ~25,000 base pairs, including ≥70 open reading frames (ORFs). Genetic variations have been identified in the genome of VZV strains (6)(7)(8)(9)(10)(11)(12)(13). Based on the specific single-nucleotide polymorphisms (SNPs) in ORFs 1, 21, 50 and 54, VZV strains have been divided into the following genotypes: A (Africa/Asia), B and C (Europe and North America), and J (Japanese) (6).…”
Section: Introductionmentioning
confidence: 99%